2021
DOI: 10.3390/s21206901
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cybersecurity Practices on Cyberattack Damage: The Perspective of Small Enterprises in Saudi Arabia

Abstract: Small and medium-sized enterprises represent the majority of enterprises globally and yet have some difficulties in understanding the impact that cybersecurity threats could have on their businesses and the damage they could do to their assets. This study aims to measure the effectiveness of security practices at small-sized enterprises in Saudi Arabia in the event of a cybersecurity attack. Our paper is among the first research papers to measure the effectiveness of cybersecurity practices and the threat pose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(17 reference statements)
0
15
1
Order By: Relevance
“…Kaila and Urpo [94] suggest the useful first steps for start-ups and SMBs should be: identifying assets and risks; protecting accounts, systems, clouds, and data; implementing a continuity plan; and monitoring and reviewing. Other researchers suggested SMBs should put more focus on practices that can decrease the impact of cyberattacks such as investing in an inspection team and a documented recovery plan [105]. It is not only the SMB's responsibility, but also technology vendors who have been challenged to incorporate security into computing technologies to assist the likes of SMBs with limited knowledge and access to expertise [26].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kaila and Urpo [94] suggest the useful first steps for start-ups and SMBs should be: identifying assets and risks; protecting accounts, systems, clouds, and data; implementing a continuity plan; and monitoring and reviewing. Other researchers suggested SMBs should put more focus on practices that can decrease the impact of cyberattacks such as investing in an inspection team and a documented recovery plan [105]. It is not only the SMB's responsibility, but also technology vendors who have been challenged to incorporate security into computing technologies to assist the likes of SMBs with limited knowledge and access to expertise [26].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…For example McLauren adopted a quantitative approach to study to which extent SMBs should implement a security framework to offer the most return on investment [28]. Alharbi et al [105] also adopted quantitative methods to measure the impact that SMB cyber security practices have on cyber-attack damage. Their research indicated that having an inspection team and a recovery plan reduced the financial damage that a cyber-attack had on SMBs in Saudi Arabia.…”
Section: E Research Methodology Usedmentioning
confidence: 99%
See 3 more Smart Citations